2017
DOI: 10.1016/j.fct.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of antioxidant and antiproliferative activities of Rhodomyrtus tomentosa extracts prepared with various solvents

Abstract: Rhodomyrtus tomentosa (Aiton) Hassk. has a wide spectrum of pharmacological effects and has been used to treat wounds, colic diarrhoea, heartburns, abscesses and gynaecopathy. The potential antiproliferative activities of R. tomentosa extracts from different solvents were evaluated in vitro on HepG2, MCF-7 and HT 29 cell lines while antioxidant activity was monitored by radical scavenging assay (DPPH), copper reducing antioxidant capacity (CUPRAC) and β-carotene bleaching assay. Extracts from R. tomentosa show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 57 publications
3
17
0
1
Order By: Relevance
“…As hydrogen donor, reactive oxygen quenchers, reducing agent and free radical scavenging agent in redox reactions, phenolic compounds are very important for antioxidant activity [38]. Our results showed that phenolics had a greater contribution to antioxidant activity than triterpenoid in the extracts of C. paliurus leaves, which confirmed the above viewpoint.…”
Section: Correlation Between Phytochemicals and Bioactivitysupporting
confidence: 84%
See 1 more Smart Citation
“…As hydrogen donor, reactive oxygen quenchers, reducing agent and free radical scavenging agent in redox reactions, phenolic compounds are very important for antioxidant activity [38]. Our results showed that phenolics had a greater contribution to antioxidant activity than triterpenoid in the extracts of C. paliurus leaves, which confirmed the above viewpoint.…”
Section: Correlation Between Phytochemicals and Bioactivitysupporting
confidence: 84%
“…Compared with other plant species, the scavenging capacity of DPPH radical and reducing power in the ethanol extracts of C. paliurus leaves were weaker than the ethanol extracts of pyrola leaves, but the scavenging capacity of ABTS was similar between the two plants from specific locations [34]. Most populations were higher than goji berry and Aspalathus Linearis and some populations were comparable to R. tomentosa in terms of the scavenging capacity of DPPH radical [36][37][38]. The scavenging capacity of ABTS of some populations was higher than specific goji berry and Solanaceae species [36,39].…”
Section: Effects Of Solvent and Geographical Origin On Antioxidant Acmentioning
confidence: 97%
“…In 2017, Hamid et al . reported that the inhibition of DPPH free radicals in the extracts depends on the concentration, and by increasing the concentration of the extract the inhibitory effect was increased . In contrast, in 2015, Erbil & Digrak observed that the free radical‐scavenging capacity of DPPH decreased with an increase in the concentrations of methanolic extract of lilac sage and balansa…”
Section: Resultsmentioning
confidence: 99%
“…The solubility of flavonoids and polyphenols can be affected by aromatic ring, glycosyl form and side chain binding. The more hydroxyl groups in the molecule, the stronger of the polarity rises, and easy to dissolve in high polar solvents 17 . The results from the study was similar to previous study that the methanol was most effective in extracting flavonoids and polyphenols from plants 18 .…”
Section: Discussionmentioning
confidence: 99%